Dual-Media Granular Filtration System for Slaughterhouse Wastewater Treatment: A Case Study in Bangladesh - Karima, Azrina; Hassan, Khondoker Mahbub (Journal of Engineering Science, 2022)
In developing countries, including Bangladesh, deliberate disposal of the untreated slaughterhouse wastewater causes environmental pollution and poses threat to public health. In this study, slaughterhouse wastewater was analyzed for the Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD5), and faecal coliforms (E. coli) were found ranging between 1,840–3,300 mg/L, 62–619 mg/L and est.>3,400– 6,00,000 CFU/100 ml, respectively. A bench-scale treatment unit, adopting activated sludge process, was developed in the laboratory and the average treatment efficiency for BOD5 and TSS were found 67% and 39%, respectively. However, the efficiency for microbial removal performance was inconclusive. An additional duel-media granular filtration unit was developed to improve the effluent quality and the treatment efficiencies for BOD5, TSS and E. coli were improved to 90% to 100%. The study highlighted the level of pollution caused by the slaughterhouse wastewater disposal to the surrounding water bodies and how the decentralized treatment approach can improve water quality. Journal of Engineering Science 13(1), 2022, 41-50